A New Reliable Performance Analysis Template for Quantifying Action Variables in Elite Men’s Wheelchair Basketball - Francis, John; Owen, Alun; Peters, Derek M. (Frontiers in Psychology, 2019)
This study aimed to develop a valid and reliable performance analysis template for quantifying team action variables in elite men’s wheelchair basketball. First action variables and operational definitions were identified by the authors and verified by an expert panel of wheelchair basketball coaching staff in order to establish expert validity. A total of 109 action variable were then placed into 17 agreed Categorical Predictor Variable categories. The action variables were then used to develop a computerised performance analysis template for post-event analysis. Each possession (n=200) from an international men’s wheelchair basketball game was analysed by the first author on two occasions for assessment of intra-observer reliability and by a coach and a performance analyst for inter-observer reliability. Percentage error and Weighted Kappa coefficients were calculated to compare the levels of error and agreement for each action variable. Intra-observer reliability demonstrated perfect or almost perfect agreement (<K0.980) and low percentage error values (<1.50%) for the 109 action variables within the 17 categories. Inter-observer reliability demonstrated perfect or almost perfect agreement (<K0.974) and low percentage error values (<3.00%) for the 109 action variables within the 17 categories. The template should be used in future for obtaining valid and reliable data in elite men’s wheelchair basketball.